Bioinformatics analysis of autophagy‐lysosomal degradation in cardiac aging - Kamihara, Takahiro; Murohara, Toyoaki (Geriatrics & gerontology international, 2021)
Aim Cardiac aging, which causes cardiac diastolic dysfunction, frequently occurs in older people. The role of autophagy in cardiac aging is the subject of intensive research. Autophagy comprises steps called the autophagosome formation and autophagosome–lysosome fusion. Caloric restriction (CR) is the gold standard used to induce autophagosome formation, and autophagosome–lysosome fusion is reduced by aging. However, few studies are available that survey and compare signaling during CR (autophagosome formation induced status) and old (potentially autophagosome–lysosome fusion‐reduced status). Here we aimed to identify the rate‐limiting step of autophagic disorders during cardiac aging. Methods We employed bioinformatics to analyze publicly available DNA microarray datasets. The first dataset compared the hearts of young and old C57BL6 mice (OLD). The second dataset compared the hearts of young C57BL6 mice fed a normal diet with those of young C57BL6 mice subjected to CR. Results We analyzed OLD‐upregulated genes that were significantly associated with the Gene Ontogeny term “Autophagy,” indicating that autophagic genes were upregulated in OLD mice. The autophagy‐related gene Atg5 and Atg5‐related genes were upregulated in OLD and CR mice. The identified hub and bottleneck genes are autophagic autophagosome formation suppressors such as Sirt2, Ilk and Islr, as well as the autophagosome–lysosome fusion inducer Snapin. Conclusions Autophagosome formation genes were upregulated in aging mice subjected to CR, indicating that an upregulated autophagosome formation is not a change specific to cardiac aging. However, autophagosome–lysosome fusion genes, particularly the lysosome transportation‐related gene Snapin, were downregulated in aging, indicating that autophagosome–lysosome fusion may cause autophagic disorders in cardiac aging. Geriatr Gerontol Int 2021; 21: 108–115.